2012
DOI: 10.1186/1472-6963-12-467
|View full text |Cite
|
Sign up to set email alerts
|

Motives for early retirement of self-employed GPs in the Netherlands: a comparison of two time periods

Abstract: BackgroundThe high cost of training and the relatively long period of training for physicians make it beneficial to stimulate physicians to retire later. Therefore, a better understanding of the link between the factors influencing the decision to retire and actual turnover would benefit policies designed to encourage later retirement. This study focuses on actual GP turnover and the determining factors for this in the Netherlands. The period 2003–2007 saw fewer GPs retiring from general practice than the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This disillusionment was expressed by a sense of frustration with colleagues [27, 35], feeling undervalued, lacking prestige [16, 41], and a loss of interest in their work [10]. Excessive workload [17, 42] and burnout were associated with intentions to retire [28, 43]. Medicolegal issues often arose from a lack of satisfaction with the regulation of medicine for reasons of unwelcome change, bureaucracy, oppressive management [26, 35, 44], and issues with physician partners [26, 45].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This disillusionment was expressed by a sense of frustration with colleagues [27, 35], feeling undervalued, lacking prestige [16, 41], and a loss of interest in their work [10]. Excessive workload [17, 42] and burnout were associated with intentions to retire [28, 43]. Medicolegal issues often arose from a lack of satisfaction with the regulation of medicine for reasons of unwelcome change, bureaucracy, oppressive management [26, 35, 44], and issues with physician partners [26, 45].…”
Section: Resultsmentioning
confidence: 99%
“…Findings based on these studies of physicians suggest that a reduction of working hours may present as one of the most successful instruments for staff retention [17]. A shift toward non-clinical duties such as teaching and mentorship may also help with retention [42] and also facilitate knowledge transfer to younger professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although current evidence points to an impending crisis in the recruitment and retention of GPs in the UK, 12 – 14 this is by no means a new phenomenon, 15 – 17 nor one which is unique to the UK workforce. 18 20 In 2001, a survey carried out by the BMA revealed that one-quarter of GPs wanted to quit, 21 while a number of surveys, carried out before and since, have continued to monitor GP training, retention, and recruitment, particularly in relation to contractual reforms, job satisfaction, and burnout. 15 , 22 26 Much research has been carried out on factors associated with stress, anxiety, depression, and burnout among doctors in the UK and abroad.…”
Section: Discussionmentioning
confidence: 99%